Free and Immobilized Microbial Culture–Mediated Crude Oil Degradation and Microbial Diversity Changes Through Taxonomic and Functional Markers in a Sandy Loam Soil - Khandelwal, Ashish; Sugavanam, Ramya; Ramakrishnan, B.; Dutta, Anirban; Varghese, Eldho; Nain, Lata; Banerjee, Tirthankar; Singh, Neera (Frontiers in Environmental Science, 2022)
Crude oil contamination of soil and water resources is a wide spread issue. Present study evaluated degradation of aliphatic hydrocarbons (C11–C36) in crude oil by 17 bacteria isolated from a crude oil contaminated soil. The results suggested that Pseudomonas sp. and Bacillus amyloliquefaciens were best hydrocarbon degrading bacteria in the presence of surfactant Tween-80 (0.1% w/v). Based on present investigation, Pseudomonas sp.+B. amyloliquefaciens and previous study, fungus Aspergillus sydowii, were identified as best oil degrader and were immobilized in alginate-bentonite bead, guargum-nanobenonite WDG and CMC-bentonite composite. Sandy loam soil was fortified with 1, 2, and 5% crude oil and total petroleum hydrocarbon (TPH) degradation efficiency of free cultures and bio-formulations was evaluated in a sandy loam soil. Compared to half-life (t1/2) of 69.7d in the control soil (1% oil), free cultures of Pseudomonas sp.+B. amyloliquefaciens and A. sydowii degraded TPH with t1/2 of 10.8 and 19.4 days, respectively. Increasing the oil content slowed down degradation and the t1/2 in the control, Pseudomonas sp+B. amyloliquefaciens and A. sydowii inoculated soils were 72.9, 14.7 and 22.2 days (2%) and 87.0, 23.4 and 30.8 days (5%), respectively. Supplementing soil with ammonium sulfate (1%) enhanced TPH degradation by Pseudomonas sp.+B. amyloliquefaciens (t1/2 - 10 d) and A. sydowii (t1/2 - 12.7 d). All three bio-formulations were effective in degrading TPH (1%) and the t1/2 were 10.7-11.9d (Pseudomonas sp.+B. amyloliquefaciens and 14-20.2d (A. sydowii) and were at par with free cultures. Microbial diversity analysis based on taxonomic markers and functional marker suggested that bio-augmentation process helped to keep soil in active stage and restored original microbial population to some extent. The present study concluded that bio-formulations of crude oil degrading microbes can be exploited for its degradation in the contaminated environment.